2012
DOI: 10.1111/j.1348-0421.2012.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐administration of live attenuated Salmonella enterica serovar Typhimurium expressing swine interleukin‐18 and interferon‐α provides enhanced Th1‐biased protective immunity against inactivated vaccine of pseudorabies virus

Abstract: The co-administration of two or more cytokines may generate additive or synergistic effects for controlling infectious diseases. However, the practical use of cytokine combinations for the modulation of immune responses against inactivated vaccine has not been demonstrated in livestock yet, primarily due to protein stability, production, and costs associated with mass administration. In light of the current situation, we evaluated the immunomodulatory functions of the combined administration of swine interleuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Furthermore, recently it is reported that recombinant chIL-18 potentiated both the humoral and cell mediated immune responses against recombinant Newcastle disease virus vaccine (21,22) which directly supports our findings. The use of attenuated S. enterica serovar Typhimurium strain χ8501 as a successful mammalian and avian cytokine genes delivery system is well addressed at our laboratory in our several recent publications (13,17,23,24). According to our published data and other related published data, it is believed that the Salmonella bacteria used for cytokine delivery can persist in chickens for 3~7 weeks, depending on age of chickens, and can provide continuous long term protection against virus infection (12,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recently it is reported that recombinant chIL-18 potentiated both the humoral and cell mediated immune responses against recombinant Newcastle disease virus vaccine (21,22) which directly supports our findings. The use of attenuated S. enterica serovar Typhimurium strain χ8501 as a successful mammalian and avian cytokine genes delivery system is well addressed at our laboratory in our several recent publications (13,17,23,24). According to our published data and other related published data, it is believed that the Salmonella bacteria used for cytokine delivery can persist in chickens for 3~7 weeks, depending on age of chickens, and can provide continuous long term protection against virus infection (12,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Interferon‐γ plays an important role in both innate and adaptive immunity and also promotes Th1 polarization. The results of this study indicate that HMGB1 is a potent inducer of IFN‐γ expression and the heterocomplex comprising both HMGB1 and LPS synergistically up‐regulates the IFN‐γ expression.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should investigate this possibility of modulating the host immune system against HIV-1 Gag antigens by the production of in vivo functional cytokines by Salmonella vaccine vectors. Biologically-active cytokines can easily be co-delivered by Salmonella [118,119]. It has already been demonstrated that recombinant Salmonella co-expressing IL-2, IFN-γ, and macrophage migration inhibitory factor with recombinant antigen could afford to protect mice challenged with Leishmania major [120].…”
Section: Opportunities For the Futurementioning
confidence: 99%